2020
DOI: 10.3390/ani10030531
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Neuroendocrine Biomarkers and Gut Microbiota in Dogs Supplemented with Grape Proanthocyanidins: Results of Dietary Intervention Study

Abstract: Several studies on the interaction between gut microbiota and diets, including prebiotics, have been reported in dogs, but no data are available about the effects of dietary administration of grape proanthocyanidins. In the study, 24 healthy adult dogs of different breeds were recruited and divided in 3 groups of 8 subjects each. A group was fed with a control diet (D0), whilst the others were supplemented with 1 (D1) or 3 (D3) mg/kg live weight of grape proanthocyanidins. Samples of feces were collected at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Briefly, dogs were recruited from different living environment for every DIS and they were undergone through diet modulation. The DIS 1 [ 12 ], 2 [ 13 ], 3 and 8 [ 14 ] were private kennels, DIS 4 [ 15 ] and 7 were shelters and DIS 5 and 6 were dogs privately owned. For every DIS, the first faecal sample (T0) was collected from dogs that were fed the usual diet they received since at least 6 months (control diet, CTR).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, dogs were recruited from different living environment for every DIS and they were undergone through diet modulation. The DIS 1 [ 12 ], 2 [ 13 ], 3 and 8 [ 14 ] were private kennels, DIS 4 [ 15 ] and 7 were shelters and DIS 5 and 6 were dogs privately owned. For every DIS, the first faecal sample (T0) was collected from dogs that were fed the usual diet they received since at least 6 months (control diet, CTR).…”
Section: Methodsmentioning
confidence: 99%
“…The 16S rRNA annotated sequences were then normalized to ‰ abundance profiles for each sample and each taxonomic level, already known as relative abundance (RA). Taxa with RA lower than 10‰ were excluded from the statistical analysis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been also demonstrated, both in human and animal models, that the microorganism inhabitants of the gut and the compounds they produce, such as short-chain fatty acids, lactic acid, and metabolites of amino acids, affect host physiology [ 3 ]. Among the others, the microbial metabolism of tryptophan and threonine and the related interaction with the availability of neurotransmitters for the host has led to the development of the brain-gut-microbiome axis concept [ 4 , 5 ]. It has also been reported that the microbiome can influence distant organs by three principal effects, regulating the nutritional absorption and production of vitamins, regulating the immune system, and translocating bacteria through the endothelial barrier and into the bloodstream [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a relationship between the gut microbiome and obesity has been observed, it remains unclear as to how the gut microbiome contributes to the development of obesity, but proposed mechanisms include the production of short chained fatty acids (SCFAs), monosaccharides, and other bioactive molecules. These bacterial products may lead to an increase in dietary energy harvest ( Turnbaugh et al, 2006 ), changes in lipid metabolism ( Ghazalpour et al, 2016 ), changes in fat storage regulation ( BĂ€ckhed et al, 2004 ; BĂ€ckhed et al, 2007 ), altered satiety ( Arora, Sharma & Frost, 2011 ), and an increase in systemic low-grade inflammation via the interaction with either the enteric nervous system ( Schwartz, 2000 ; Tehrani et al, 2012 ; De Lartigue, De La Serre & Raybould, 2011 ), the endocrine system ( Mondo et al, 2020 ; Kirchoff, Udell & Sharpton, 2019 ; Scarsella et al, 2020 ), or the immune system ( Cani et al, 2007 ; Cani et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%